A hydrophobic and abrasion-resistant MgF2 coating with an ultralow refractive index for double-layer broadband antireflective coatings. Issue 12 (10th March 2017) - Cui, Xinmin; Ding, Ruimin; Wang, Mengchao; Wang, Conghui; Zhang, Jing; Wang, Jing; Dong, Wensheng; Xu, Yao
Abstract : A novel sol–gel route was proposed in order to prepare an ultralow-index MgF2 coating with both hydrophobicity and good abrasion-resistance. Abstract : An ultralow-index top layer is a prerequisite to preparing high-performance broadband AR coatings. When coupled with hydrophobicity and the abrasion-resistance required in practical applications, the challenge becomes even greater. In this work, a MgF2 AR coating was studied because of the low refractive index of MgF2 and its easily realized strong adhesion through low-temperature heat treatment. In order to obtain an ultralow refractive index and endow the coating with hydrophobicity, we designed several experimental routes and finally adopted MTES/TEOS co-precursors to direct MgF2 particles to form a honeycomb-like network structure without a template. A final refractive index of 1.15 and good hydrophobicity, with a water contact angle of 122°, were obtained using the MgF2 –SiO2 (CH3 ) coating. These superior properties were attributed to the incorporation of methyl groups, which not only endowed the coating with hydrophobicity, but also changed the original linear assembly of MgF2 particles to a circular assembly. Using this hydrophobic ultralow-index coating as a top layer, a high-performance double-layer AR coating was fabricated with a high average transmittance of 99.43% in the wavelength range of 400–1000 nm, good abrasion-resistance, and damp heat resistance after a low-temperature heat treatment of 250 °C. This MgF2 double-layer AR coating may be used in display devices or lenses.